HUBUNGAN ANTARA KOORDINASI MATA – TANGAN DENGAN KEMAMPUAN SERVIS DALAM PERMAINAN BULU TANGKIS PADA S I S W A KE LA S V S D N PETEMON KECAMATAN KOPANG KABUPATEN LOMBOK TENGAH TAHUN PELAJARAN 2014 / 2015 - Zohri Zohri (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2016)
The game of badminton in Indonesia is a sport loved by the people, in addition to football, volleyball and a variety of sports lainnya.Teknik service is one technique that must be mastered, because the service was the first attack in the game of badminton. If the service is wrong, then the enemy will benefit by earning points, especially now uses rally scoring  system  point.oleh  Therefore,  the  ability  of  service  is  needed  in  the  game  of badminton. Eye coordination and good hand is also advantageous to be able to drive the ball hitting the ball the way he wanted to do engineering service. The problems in this study is whether there is relationship between Eye Coordination - The hand with Serviceability in Badminton  Games  in  Class  V  SDN  Petemon  Kopang  Central  Lombok  District  of  the Academic Year 2014/2015? While the purpose of the research was to find out relationship between Eye Coordination - The hand with Serviceability in Badminton Games in Class V SDN Petemon Kopang District of Central Lombok regency in the academic year 2014 /2015. Population in this study were all students of class V SDN Petemon son Kopang District Subdistrict Central Lombok in the school year 2014/2015, amounting to 15 students, while the researchers used a sample of 100% so that the sampling technique used in this research is the study populasi.Untuk obtain the data necessary to support the success of the research, it is necessary a method for data collection. In accordance with the objectives of this study, the method used is the test method works to obtain data using a hand eye coordination test caught throwing a baseball from the walls and the ability to service service. from measured using test data analysis obtained by value "rxyhitung amounted to 0.670, while the magnitude of the numbers r table with a significant level of 5% and N = 15 is 0.514. This means that r count is greater than r table (0.670> 0.514) so it concluded that "there is a relationship between eye coordination - Hand with Serviceability in Badminton Games in Class V SDN Petemon Kopang Central Lombok District of Academic Year 2014/2015 ,